A novel two-dimensional transition metal dichalcogenide as water splitting photocatalyst with excellent performances - Wang, Fang; Cheng, Zishuang; Zhang, Xiaoming; Xie, Chunxiao; Liu, Fucai; Chang, Chuntao; Liu, Guodong (Frontiers in Chemistry, 2022)
With the rising demand for renewable energy, photocatalysts are considered the most promising solution to harness solar energy, and the search for photocatalysts with excellent performances remains an urgent task. Here, based on density functional theory (DFT), the photocatalytic properties of MoWS4 are systematically investigated. The MoWS4 monolayer and bilayer are demonstrated as semiconductors with indirect band gaps of 2.01 and 1.48 eV. Moreover, they exhibit high and anisotropic light absorption coefficients of up to ∼105 cm−1 in the visible-ultraviolet region. The intrinsic band edge positions could fully satisfy the redox potentials of water without any external adjustment. The electron mobility of MoWS4 monolayer is 557 cm2 V−1s−1, which is seven times higher than MoS2 monolayer. Hence, MoWS4 can be regarded as a promising 2D photocatalyst candidate for water splitting.